O efeito da motivação sobre a intenção de empreender através do marketing multinível no Brasil: um estudo exploratório baseado na Teoria da Expectância - Devitte Junior, Jorge Antonio (2019)
Cultural, demographic and social changes affect the way products and services are distributed. Networking marketing is a kind of direct selling and it emerges as an efficient distribution channel. These organizational salesforce is formed only by independent agents who buy, sell and recruit other individuals for their own salesforce. The aim of this study is to understand how motivation and satisfaction affect entrepreneur’s efforts. The Expectancy Theory was used to build a theoretical model to check it. The research was conducted in two phases. First, a qualitative study was done with experienced entrepreneurs and executives of network marketing. As for the second phase, a quantitative study was done with entrepreneurs of a networking marketing startup. The results demonstrate and confirm that motivation affects entrepreneurs’ efforts positively, but in contrast to Expectancy Theory and previous understandings that show that satisfaction do not affect these individuals’ efforts. We believe that the model developed and the results obtained will help network marketing companies to develop programs and initiatives to improve their entrepreneur´s performance.